DIGITAL LITERACY AND EDUCATORS OF ISLAMIC EDUCATION - Sunarti Suly Eraku; Mohamad Karmin Baruadi; Samuel PD Anantadjaya; Siti Fadjarajani; Ucup Supriatna; Ardian Arifin (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
From the teacher's approach to students to the use of media in learning, the learning process has changed dramatically in this digital era. Islamic Religious Education teachers must improve their competence due to the stigma that they are "old teachers" who have difficulty keeping up with developments in the world of information and technology in learning. The purpose of this research is to describe the competence of Islamic Religious Education teachers in the digital age. As a result, the study clearly discusses the competence of teachers and learning in the digital era, as well as the challenges, as well as the strategies of Islamic Religious Education teachers in overcoming the challenges of learning in the digital era. A literature review from several journals and related references was used to demonstrate how a teacher should be in the digital era. Teachers in the digital age must be able to use an information and communication technology-based learning approach to make it easier for students to follow because the information they receive from cyberspace is extremely fast. Finally, Islamic Religious Education teachers must improve their ability to use technology and information-based learning media in the classroom and move away from textbooks. So that the learning process achieves its objectives and provides students with numerous opportunities to develop their learning creativity.